Guaiasistanol: A new guaiane sesquiterpenoid from Teucrium persicum Boiss - Miri, A; Sharifi-Rad, J (Cellular and Molecular Biology, 2015)
In this study, a new guaiane type skeleton sesquiterpenoid named guaiasistanol (6Î±, 10Î±-epoxy-4Î±-hydroxyguaiane) was isolated from chloroform part of the Teucrium persicum extract, also chrysothol. Spectroscopic means explained the structures. This compound was evaluated for inhibitory activity against acetylcholinesterase and it showed a moderate activity with 28% inhibition.